POLA KARIR APARATUR SIPIL NEGARA (ASN) BERBASIS MANAJEMEN TALENTA - Arief Febrianto (Polteknik Imigrasi, 2021)
Talent management is an HR management system that includes the stages of acquisition, development, retention, and placement of employees who are prioritized based on the highest potential and performance (high potential and high performance) through an assessment mechanism. Talent management complements and supports the implementation of a merit system, both in the institutional and national scope. This literature research wants to describe how the career pattern of Apparatus Human Resources is designed in such a way, especially using talent management. This research is able to become a comprehensive reference for the state civil apparatus (ASN).